Angela Leonardi, Il pensiero e la visione. Virginia Woolf saggista, Pisa, Pacini, 2021, 224 pp., € 19,00. - Scamardella, Marianna (Status Quaestionis, 2024)
Angela Leonardi, Il pensiero e la visione. Virginia Woolf saggista, Pisa, Pacini, 2021, 224 pp., € 19,00.